PENGGUNAAN ATRAKTAN ORGANIK YANG DIPERKAYA PESTISIDA KIMIA UNTUK PENGENDALIAN HAMA WALANG SANGIT SKALA LABORATORIUM - Kusmawati Kusmawati; Apriyadi R; Asriani E (Universitas Teuku Umar, 2020)
Rice ear bug is a pest which potentially sucks the ripe rice grains, therefore the grain will not be fulfilled or even empty. The usage of organic attractant with the enrichment of chemical pesticide is one of the alternatives to control the rice ear bug.The purposes of this research are to discover the preference of rice ear bug toward the organic attractant and to determine the most effective organic attractant that able to control the rice ear bug in laboratory.The research had been conducted on December 2018 until January 2019, located in experimental garden and research, faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung.This research used experimental method by treating the salted fish attractant, crab, and shrimp.Data was analyzed using Kruskal-Wallis test, descriptive quantitative, and qualitative data will be shown in score and picture.The number and mortality index of rice ear bug on salted fish attractant shows the highest, but not significant different with the shrimp attractant.The number of rice ear bug respectively on salted fish, crab, and shrimp are nineteen, four, and thirteen individuals. Keywords : Rice ear bug,Organic Attractant, Preference